Experimental investigation of the impact of macroalgal mats on the wave and current dynamics. (July 2016) - Tambroni, N.; Figueiredo da Silva, J.; Duck, R.W.; McLelland, S.J.; Venier, C.; Lanzoni, S.
Abstract: Macroalgal mats of Ulva intestinalis are becoming increasingly common in many coastal and estuarine intertidal habitats, thus it is important to determine whether they increase flow resistance, promote bed stability and therefore reduce the risk of erosion favoring tidal flooding or degradation of coastal lagoons. Venier et al. (2012) [6] studied the impact of macroalgal mats of Ulva intestinalis on flow dynamics and sediment stability for uniform flow. Here we extend their experimental work to the case of vegetation under the combined action of waves and currents. These hydrodynamic conditions are very common in many shallow coastal environments and lagoons. The experimental facility employed in the present study and the series of flow runs are the same as that used by Venier et al. (2012)[6]. However, waves have been superposed to uniform current flowing firstly over a mobile sediment bed covered with U. intestinalis, then over a bare sediment surface. For the depth, wave and current conditions considered in the experiments, the time-averaged vertical profile of horizontal velocity for the case of coexisting waves and current turns out to be very close to that observed for a pure current, both with and without vegetation. However, contrary to what was observed in the case of a unidirectional current, in the presence of waves the time averaged velocity profile is only weakly influenced by the vegetation, whose main effect is to attenuate velocity oscillations induced by waves and to slightly increase the overall bed roughness.